NILAI SMALL DENSE LDL REMAJA DAN KAITANNYA DENGAN LIPID LAINNYA - S Aprianti; M. Arif; Nurahami Nurahmi; Hardjoeno Hardjoeno (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2006)
In Indonesia, coronary heart disease (CHD) as the cause of death is still the highest in number. It is estimated that the numberof deaths is about 535 per 100.000 population. Atherosclerosis represents the main risk factor which could be predicted through thepresence of small dense LDL (sdLDL) in youngsters. To determine the value of sdLDL in youngsters and its correlation with other lipids,a study was conducted cross sectionally in Makassar, from January to August 2006, on 125 youngsters aged 15 to 19 years. Their totalcholesterol, HDL, LDL, TG and ApoB was determined and sdLDL was derived from calculation of LDL/apoB ≤ 1.2. 69 (55.20%) patientsshowed sdLDL value and 56 (44.8%) patients did not show sdLDL value. Statistical calculation showed a significant correlation betweensdLDL and HDL level (p = 0.001), sdLDL and TG level (p = 0.003), and sdLDL and ApoB level (p = 0.036). Percentage of sdLDL valuewas higher in youngsters aged 15 to 19. This proves that the process of atherosclerosis happened early at a young age. Showed by theexistence of sdLDL and therefore sdLDL could be used as a predictor of atherosclerosis which can be prevented if detected earlier.